(untitled) (Journal of International Law and Jurisprudence, 2020)
The nature of adaptation and codification means more than the eye can meet. It envisages on a complex matrix of law making and consolidation of laws in a society. Owing to the exponentially increase in the population of the society, novel transactions and vices are bound to arise. It is on this stead that it becomes imperative to make laws in tandem with modern day realism. However, for there to be a proper harmonization and uniformity in these laws, codification of laws becomes a desideratum. In certain happenstances, the legislative arm of government has not been up and doing in its legislative responsibility of law making as shall be demonstrated in the course of this paper. Thus, this paper adopted the doctrinal research methodology with the aim of examining the effects of codification and adaptation in Nigerian jurisprudential studies, vis-à-vis the nexus between codification and customary law. This paper concludes with veritable suggestions that are imperative to the Nigerian legal system.